2017
DOI: 10.1186/s12917-017-1287-x
|View full text |Cite
|
Sign up to set email alerts
|

Paraffin immunofluorescence for detection of immune complexes in renal biopsies: an efficient salvage technique for diagnosis of glomerulonephritis in dogs

Abstract: BackgroundRenal biopsy is an essential tool for the diagnosis of proteinuric kidney diseases in dogs, and evaluation of immune complexes (IC) by immunofluorescence (IF) of frozen sections (IF-F) is required for the diagnosis of IC-mediated glomerulonephritis (ICGN). However, the use of frozen sections from renal biopsies can have limitations. The aim of this study was to develop a reliable IF method using formalin-fixed and paraffin-embedded (FFPE) sections to detect ICs in dog ICGN.MethodsRenal biopsy specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…Because formalin fixation induces protein cross-linking, which generally blocks antigenicity, an antigen-retrieval step that allows for increased penetration of antibodies to the antigens “masked” by formalin fixation is required in IF-P. 5 , 6 This step involves incubating the paraffin sections with a proteolytic enzyme or heating the sections before incubation with fluorescein isothiocyanate–conjugated antibodies against Igs and complement components. Multiple proteolytic enzymes have been used in IF-P, including trypsin, 7 , 8 , 9 , 10 , 11 , 12 pronase E (protease XIV), 13 , 14 , 15 , 16 , 17 proteinase XXIV, 18 and proteinase K. 13 , 19 , 20 , 21 , 22 Successful results were also obtained by heat treatment with Tris or citrate buffers 15 and with dual microwave heating in EDTA antigen-retrieval solution. 23 In our laboratory, we use the pronase technique, which was originally described by Fogazzi et al.…”
Section: Methodologies Of Paraffin Immunofluorescencementioning
confidence: 99%
See 1 more Smart Citation
“…Because formalin fixation induces protein cross-linking, which generally blocks antigenicity, an antigen-retrieval step that allows for increased penetration of antibodies to the antigens “masked” by formalin fixation is required in IF-P. 5 , 6 This step involves incubating the paraffin sections with a proteolytic enzyme or heating the sections before incubation with fluorescein isothiocyanate–conjugated antibodies against Igs and complement components. Multiple proteolytic enzymes have been used in IF-P, including trypsin, 7 , 8 , 9 , 10 , 11 , 12 pronase E (protease XIV), 13 , 14 , 15 , 16 , 17 proteinase XXIV, 18 and proteinase K. 13 , 19 , 20 , 21 , 22 Successful results were also obtained by heat treatment with Tris or citrate buffers 15 and with dual microwave heating in EDTA antigen-retrieval solution. 23 In our laboratory, we use the pronase technique, which was originally described by Fogazzi et al.…”
Section: Methodologies Of Paraffin Immunofluorescencementioning
confidence: 99%
“…Studies performed as early as the 1970s have shown that IF-P is a valuable salvage technique in renal pathology when frozen tissue is inadequate (e.g., lacks glomeruli) or not available. 8 , 10 , 14 , 18 , 20 , 21 Overall, diagnostic results by IF-P can be obtained in >80% of cases, 14 , 18 , 20 , 21 but the diagnostic yield varies depending on 3 factors: (i) The antigen-retrieval method used: proteinase K, pronase, proteinase XXIV, and dual microwave heating appear to be more sensitive than the other methodologies, although a systematic study comparing the diagnostic yield of these methods side by side on the same cohort of cases has yet to be performed. (ii) The disease type: the best results are obtained in dysproteinemia-associated kidney diseases ( Table 2 ).…”
Section: Methodologies Of Paraffin Immunofluorescencementioning
confidence: 99%
“…For the purpose of antigen retrieval, the enzymes trypsin, pepsin, protease VII, pronase, protease XXIV, and proteinase K are employed for different periods, temperatures, and concentrations. Achieving ideal digestion to unmask the antigen locations is the most important step in using an enzyme technique to perform DIF on formalin-fixed renal biopsies [ 22 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, several innovations have also been made for immunofluorescence, examples of these strategies include increasing antibody permeabilization [2,15,24,25]; remotion of aldehyde excess [15]; background reduction, avoiding the artifact's increase of the signal-to-noise ratio, as well as antibody specificity [2,15]; epitope retrieval by proteolytic and/or heat treatments [24,26,27]; fixation improvements and organic degradation [28,29]; avoiding the dephosphorylation of proteins [30]; deep antibody penetration into "hidden" structures [31]; and enhancing antibody signals in an entire and well-preserved retina structure [32].…”
Section: Drawbacks In Immunolabeling Methodsmentioning
confidence: 99%
“…Drawbacks to Face Disadvantages to face that are presented in (Figure 1): 7-9, 14 and 15. Yabuki et al [26] applied a combination of heat and proteolytic antigen retrieval methods. One of the most common consequences of the formaldehyde fixation is the crosslinking of methylene bridges between formaldehyde and proteins [56], making it impossible for antibodies to reach the epitopes of proteins, leading to weak specific signals of immunofluorescence staining and favoring the high background given by false-positive staining if an antigen retrieval step is not applied before the immunofluorescence method.…”
Section: Key Pointsmentioning
confidence: 99%